Introducing the Penn State World Campus through Certificate Programs in Turfgrass Management and Geographic Information Systems - Alfred Turgeon; David DiBiase; Gary Miller (Online Learning, 2019)
This paper describes two of the distance educational programs—Turfgrass Management and Geographic Information Systems—offered through the Penn State World Campus during its first year of operation in 1998. Detailed information is provided on how these programs were selected and supported, the nature of the students who enrolled and the faculty who developed and taught the courses, and the technology and infrastructure employed for delivering content and engaging students in collaborative learning. The organization of the World Campus, the evolution of these programs, and the results obtained from them during the first 18 months of operation are presented. Several contemporary issues are addressed from a faculty perspective, including: teaching effectiveness, relationship with students, satisfaction with product, compatibility with other responsibilities, ethical concerns, incentives and rewards, team efforts, support services, perceptions by colleagues, scholarly value, opportunity cost for faculty, intellectual property concerns, and compensation.